Distribution and bioaccumulation of polychlorinated dibenzo‐p‐dioxins and dibenzofurans in the tissues of Yorkshire pig. Issue 11 (13th October 2022) - Zhang, Xuli; Wang, Liang; Liu, Xiaofang; Liu, Xiao; Cao, Wencheng; He, Jingyi; Fan, Jingli; Wen, Sheng; Zhou, Yan
Abstract : Abstract: Polychlorinated dibenzo‐ p ‐dioxins and dibenzofurans (PCDD/Fs) in various foods continuously concern the public. Pork and its byproducts, especially from Yorkshire pigs, are the largest meat food consumed by the general population in China. This study aims to investigate the distribution of PCDD/Fs in different tissues of Yorkshire pigs to understand their bioaccumulation. Yorkshire pigs were fed a known amount of PCDD/Fs through fly ash. PCDD/Fs were determined by isotope dilution method with a gas chromatography‐high resolution mass spectrometer. The liver had the highest concentration levels (2041.33 pg/g lipid) and toxic equivalents values (69.14 pg/g lipid), followed by the spleen and lung, and the lowest ones in the brain. The liver also had the highest bioaccumulation of PCDD/Fs, and this level was considerably higher than that of other tissues. This study showed a strong accumulation capacity of the liver for polychlorinated dibenzo‐ p ‐dioxins and dibenzofurans under short‐term exposure conditions, suggesting that the liver is a more sensitive tissue for monitoring PCDD/Fs in food safety risk monitoring. Practical Application: This paper may help the consumer in making food choices to minimize the exposure risk to Polychlorinated dibenzo‐ p ‐dioxins and dibenzofurans.